3, 4, 5-Trinitro-1-(nitromethyl)-1H-pyrazole (TNNMP): a perchlorate free high energy density oxidizer with high thermal stability. Issue 21 (15th May 2017) - Kumar, Dheeraj; Imler, Gregory H.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract : A rare high energy density oxidizer with excellent thermal stability along with good oxygen balance and energetic properties was synthesized and fully characterized. Abstract : A superior oxidizer, a derivative of trinitropyrazole, 3, 4, 5-trinitro-1-(nitromethyl)-1 H -pyrazole (TNNMP), was obtained in good yield by the reaction of ammonium 4-amino-3, 5-dinitropyrazolate with bromonitromethane followed by oxidation with a mixture of H2 O2 /H2 SO4 . Characterization of TNNMP shows that in addition to having good oxygen balance (+18.3%) and detonation performance ( D v = 8858 m s −1 ; P = 35.1 GPa), it concomitantly has high thermal stability ( T d = 202 °C) and acceptable sensitivities (IS = 14 J; FS = 120 N). These attractive properties suggest TNNMP as a promising perchlorate free high energy density oxidizer and a potential replacement for ammonium perchlorate.